SYSTEMIC LUPUS ERYTHEMATOSUS : CASE REPORT - Tri Wedari, Ida Ayu (E-Jurnal Medika Udayana; vol 3 no 2 (2014):e-jurnal medika udayana, 2014)
Systemic lupus erythematosus (systemic lupus erythematosus, SLE), an autoimmune disease characterized by the production of antibodies against components of the cell nucleus that is associated with a broad clinical manifestations. Ninety percent of cases of systemic lupus erythematosus attacking a young woman with a peak incidence at 1540 years of age during the reproductive period with the ratio of women and men 5:1. Its etiology is unclear, allegedly associated with a specific immune response genes in the major histocompatibility complex class II, HLA-DR2 and HLA DR3. Clinical manifestations which appear heterogeneous and involve almost all organ systems of the condition of the joints and skin of patients with mild to severe disease that attacks the central nervous system, lungs, gastrointestinal tract, and kidneys. Treatment is mainly aimed at controlling the symptoms of the acute attack and suppress symptoms and weight at a level that can be tolerated and prevent organ damage.
Keywords: Systemic Lupus Erythematosus